‘Anti-essentialism and digital humanities: a defense of the field against epistemological challenges’ - Siraprapa Chavanayarn (Cogent Arts & Humanities)
This article defends Digital Humanities (DH) against important epistemological challenges questioning its place within the humanities. It emphasizes that while DH incorporates digital technologies, notably AI technologies, it remains fundamentally aligned with the humanities through its focus on understanding and appreciating the creation of human-made things such as literature, philosophy, and culture. Addressing epistemic critiques of DH’s knowledge characteristics, its supportive roles in research, and the efficacy of its tools, the article advocates an anti-essentialist viewpoint. This approach proposes that DH’s diverse methodologies enrich rather than dilute the humanities. By applying the idea of anti-essentialism, especially Wittgenstein’s notion of family resemblance, to understanding the concept of humanities, the article argues for a broader, more inclusive understanding of the humanities, underscoring DH’s legitimate role in this evolving field.